Sapogenin triterpene intermediates - PHARM, CENTRE D'ETUDES POUR L'IND (1966)
Process for extracting sapogenin triterpene complexes from plants, incl. Hedera helix. The complexes are used as intermediates for pharmaceuticals. Plants other than Hedera helix are e.g. Platanus orientales L., Betula alba, Quercus Suber L, Myrica ale L, Papaver somniferum L. etc. The plant material (pref. a wood) is ground to a fine powder and extracted by refluxing with water-alcohol (50-70% alcohol) in amt. of 4-8 lt. solvent/kg. wood powder. Supernatant is centrifuged off, and absolute alcohol added to ppte. water solubles, which are removed, and supernatant evap. to dryness, and residue extracted with acetone. The extract is then evap. to dryness to obtain the desired complex.
Keywords: extraction technique; plant material; Wood